Lower Bounds for Eigenvalues of the Stokes Operator (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we propose a condition that can guarantee the lowerbound property of the discrete eigenvalue produced by the finite elementmethod for the Stokes operator. We check and prove this conditionfor four nonconforming methods and one conforming method.Hence they produce eigenvalues which are smaller than their exactcounterparts.